Shale Boom : The Barnett Shale Play and Fort Worth - Hinton, Diana Davids, 1943- (Book collections on Project MUSE., 2018)
Shale Boom: The Barnett Shale Boom in North Texas is a study of the opening up of the Barnett Shale to enormous gas production and how that led to an urban gas drilling boom in the Fort Worth metroplex.